2018
DOI: 10.1128/mcb.00504-17
|View full text |Cite
|
Sign up to set email alerts
|

MafB Is Critical for Glucagon Production and Secretion in Mouse Pancreatic α Cells In Vivo

Abstract: The MafB transcription factor is expressed in pancreatic α and β cells during development but becomes exclusive to α cells in adult rodents. -null ( ) mice were reported to have reduced α- and β-cell numbers throughout embryonic development. To further analyze the postnatal function of MafB in the pancreas, we generated endocrine cell-specific ( ) and tamoxifen-dependent ( ) knockout mice. mice exhibited reduced populations of insulin-positive (insulin) and glucagon cells at postnatal day 0, but the insulin ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…This cluster was also enriched with genes involved in ER stress ( Figure 5J , DDIT3 , ATF3 , ATF4 , and HSPA5 ). Similar to the beta ER stress population, these alpha cells also expressed significantly lower levels of genes necessary for proper function: 20, 21 GCG , ISL1 , ARX , and MAFB ( Figure 5K ). A recent study 22 reported ER stress in alpha cells in mice and linked the stress to dysfunctional glucagon secretion.…”
Section: Resultsmentioning
confidence: 91%
“…This cluster was also enriched with genes involved in ER stress ( Figure 5J , DDIT3 , ATF3 , ATF4 , and HSPA5 ). Similar to the beta ER stress population, these alpha cells also expressed significantly lower levels of genes necessary for proper function: 20, 21 GCG , ISL1 , ARX , and MAFB ( Figure 5K ). A recent study 22 reported ER stress in alpha cells in mice and linked the stress to dysfunctional glucagon secretion.…”
Section: Resultsmentioning
confidence: 91%
“…Given these findings, we identified the direct target genes of MafB, including F4/80, AIM, C1qa, C1qb, C1qc, and MSR1, by using Mafb f/f: :LysM-Cre mice ( helper cells, and rhodopsin in rod cells [30,33,34,38,49,82]. Consequently, if the target genes of MafB in macrophages are found, the unknown functions of macrophages can be clarified.…”
Section: The Phenotype Of Mafb-deficient Macrophages and Mafb Target mentioning
confidence: 99%
“…For instance, c-Maf regulates the interleukin (IL) 4 (IL4) gene in helper T cells, the IL10 gene in macrophages, and crystallin genes in lens fiber cells [7,34,38]. MafB also regulates glucagon gene expression in pancreatic α cells, the PTH gene in the parathyroid gland, and C1q genes in macrophages [30,33,74]. Thus, this indicates that large Mafs regulate critical genes that define their cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Cell counting was performed as previously described [26]. Briefly, tdsRed-positive, glucagon-positive; td-sRed-positive, glucagon-negative; insulin-positive; glucagon-positive; aRX-positive; and glucagon-positive, aRX-positive cells in each islet were counted manually in the microscopy images taken as described in the immunohistochemical staining section.…”
Section: Cell Countingmentioning
confidence: 99%
“…Mafb binds to the g1 element of the Gcg promoter together with other transcription factors, activating transcription of the Gcg gene and conferring α-cell specificity [4]. Recently, our laboratory demonstrated that Mafb is essential for glucagon production and secretion in mouse pancreatic α-cells after birth by using endocrine cellspecific Mafb-deficient models, Mafb f/f ::Ngn3-Cre (Mafb ΔEndo ) and Mafb f/f ::CAGG-CreER (Mafb ΔTAM ) mouse models [26]. However, using a pancreatic-specific Mafb conditional knockout (Mafb f/f ::Pdx1-Cre, Mafb Δpanc ) mouse model, Conrad et al reported a resto-ration of glucagon-positive α-cell count and islet glucagon content by 2 weeks and 8 weeks of age, respectively [12].…”
Section: Introductionmentioning
confidence: 99%